INTERACTION OF AIR TRANSPORTATION AND FUEL-SUPPLY COMPANIES - I. P. Zheleznaya (Научный вестник МГТУ ГА)
The article describes the role of aviation fuel in the life of air transport. Fueling industry worldwide solves two main tasks - ensuring the safety and economy of air traffic. In Russia, there is one more task of airlines fuel supply. The article deals with fuel pricing taking into consideration today's realities.